Potential of Polydatin Against Ischemia-Reperfusion Injury: New Insights from Pharmacological-Pathological Mechanism Associations - Sun Z; Wang X; Pang X (Drug Design, Development and Therapy)
Zhicheng Sun,1– 3 Xiyang Wang,1– 3 Xiaoyang Pang1– 3 1Department of Spine Surgery, Xiangya Hospital of Central South University, Changsha, People’s Republic of China; 2Hunan Engineering Laboratory of Advanced Artificial Osteo-Materials, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 3National Clinical Research Center of Geriatric Disorders, Xiangya Hospital of Central South University, Changsha, People’s Republic of ChinaCorrespondence: Xiaoyang Pang, Department of Spine Surgery, Xiangya Hospital of Central South University, Changsha, People’s Republic of China, Email xiaoyangpang@163.comAbstract: Ischemia-reperfusion injury is a multi-tissue/organ susceptible and highly destructive disease. The complex pathological mechanisms of ischemia-reperfusion injury make its prevention and treatment highly challenging, and the development of novel drugs with pharmacological pleiotropy that can target multiple pathological mechanisms has become the focus of current drug research. Polydatin is a traditional Chinese medicine monomer with pleiotropic pharmacological effects, and existing research evidence suggests that polydatin has strong protective potential against ischemia-reperfusion injury. However, the mechanism of polydatin against ischemia-reperfusion injury is still unclear. In this review, the extensive pharmacological-pathological mechanism associations between polydatin and ischemia-reperfusion injury have been described from the perspectives of inflammatory response, oxidative stress, apoptosis, autophagy, ferroptosis, and cellular pyroptosis, which will provide references to the basic and applied research of polydatin in the field of ischemia-reperfusion injury.Keywords: polydatin, ischemia-reperfusion injury, pharmacological mechanism, pathological mechanism